A Method for the Late‐Stage Formation of Ketones, Acyloins, and Aldols from Alkenylstannanes: Application to the Total Synthesis of Paecilonic Acid A. (21st April 2017) - Sommer, Heiko; Hamilton, James Y.; Fürstner, Alois
Abstract: Treatment of alkenylstannanes with Cu(OAc)2 /Et3 N affords the corresponding enol esters or ketones under conditions that proved compatible with many common functionalities; these include groups that would neither survive under the standard Tamao–Fleming conditions for the oxidation of C sp 2 −SiR3 bonds nor under the conditions commonly used to oxidize C−B bonds. Chiral centers adjacent to the unveiled carbonyls are not racemized and competing protodestannation is marginal, even if the substrate carries unprotected −OH groups as internal proton sources. Therefore, the procedure is well suited for the preparation of acyloin and aldol derivatives. These enabling virtues are illustrated by a concise approach to the bicyclic lipid paecilonic acid A.